PENGABDIAN MASYARAKAT DALAM PEMBINAAN IMAN KRISTEN TERHADAP PRAKTIK JUDI ONLINE DI INDONESIAN CHRISTIAN FELLOWSHIP (ICF) POIPET KAMBOJA - Hery Budi Yosef; Fetrie JL Maramis; Jelita Sihite; Kiki Apriani Ester Daeli (CV. Denasya Smart Publisher, 2026)
This research examines Phenomenon widespread phenomenon of online gambling in the digital era and has had significant social, economic, and spiritual impacts, including within church communities. This community service activity aims to improve understanding of Christian faith and self-control regarding online gambling practices in the Indonesian Christian Fellowship (ICF) community in Poipet, Cambodia. The method used was Participatory Action Research (PAR) through a participatory and reflective approach, involving approximately 30 members of the congregation members. The program was implemented in the form of digital literacy seminars, faith training classes, reflective discussions, and individual spiritual mentoring. Qualitatively, participants reported increased spiritual awareness, moral responsibility, and positive changes in digital behavior. These results indicate that community-based faith training is effective in strengthening religious values ​​and reducing risky behavior. This program is expected to serve as a model for replication by churches and other religious institutions facing similar challenges in the modern context.